Rehabilitation and soil conservation of degraded land using sengon (Falcataria moluccana) and peanut (Arachis hypogaea) agroforestry system - SRI SARMINAH; KARYATI KARYATI; KARMINI KARMINI; JHONATAN SIMBOLON; ERIKSON TAMBUNAN (Society for Indonesian Biodiversity, 2018)
Sarminah S, Karyati, Karmini, Simbolon J, Tambunan E. 2018. Rehabilitation and soil conservation of degraded land using sengon (Falcataria moluccana) and peanut (Arachis hypogaea) agroforestry system. Biodiversitas 19: 222-228. Rehabilitation and soil conservation effort on degraded lands is not always a success. Multiple factors, such as the field’ biogeophysical conditions and the choice of suitable plant species determine the effectivity of the rehabilitation program. Our research aimed to implement agroforestry system of sengon (Falcataria moluccana) and peanut (Arachis hypogaea) on degraded land at different soil slopes (a steep and a slightly steep slope gradient) and to analyze the effect of the system on silvicultural and hydro-orological aspects of the degraded land. The silvicultural parameters examined in this study were the ground coverage of peanut growth and the stem diameter and height of sengon trees. Meanwhile, the hydro-orological parameters included potential erosion rate, erosion hazard index, and erosion hazard level. Our study revealed that on the land with the slightly steep slope (15-25%), the survival rate of sengon reached 90%, the ground coverage of the peanuts was 70-80%, the diameter and height increment of sengon trees reached 2.47 cm/year and 17.58 cm/year, respectively. Meanwhile, the potential erosion rate was 20.05 ton/ha/year, with an erosion hazard index of 0.80 (low) and a low hazard level. In the steeper ground (25-40%), the survival rate of sengon reached 90%, the peanut coverage was 50-60% and the diameter and height increment of the sengon were 2.37 cm/year and 16.41 cm/year, respectively. In the steep ground, potential erosion rate was 45.50 ton/ha/year, with an erosion hazard index of 3.25 (moderate) and a low hazard level. We concluded that the rehabilitation and soil conservation using sengon-peanut agroforestry system effectively suppressed erosion rate to a low erosion hazard.